2000
DOI: 10.1038/sj.cdd.4400626
|View full text |Cite
|
Sign up to set email alerts
|

c-Abl: activation and nuclear targets

Abstract: The c-Abl tyrosine kinase and its transforming variants have been implicated in tumorigenesis and in many important cellular processes. c-Abl is localized in the nucleus and the cytoplasm, where it plays distinct roles. The effects of c-Abl are mediated by multiple protein-protein and protein-DNA interactions and its tyrosine kinase domain. At the biochemical level, the mechanism of c-Abl kinase activation and the identification of its target proteins and cellular machineries have in part been solved. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 71 publications
2
110
1
1
Order By: Relevance
“…Upon SH3 domain binding to the PxxP motif, c-Abl might undergo modulation (32), however because c-Abl activation precedes PPARγ2 accumulation, there must be an alternative means of c-Abl activation. c-Abl is known to be activated physiologically by DNA damage response elements like ataxia telangiectasia mutant (ATM) protein (33).…”
Section: Discussionmentioning
confidence: 99%
“…Upon SH3 domain binding to the PxxP motif, c-Abl might undergo modulation (32), however because c-Abl activation precedes PPARγ2 accumulation, there must be an alternative means of c-Abl activation. c-Abl is known to be activated physiologically by DNA damage response elements like ataxia telangiectasia mutant (ATM) protein (33).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 It has been demonstrated that c-ABL inhibits IkBa degradation by inducing its accumulation in the nucleous. 31,32 c-ABL is a protein that actively shuttles between the cytoplasm and the nucleus. 33 Interestingly IkBa also actively undergoes nucleus-cytoplasm shuttling.…”
Section: Discussionmentioning
confidence: 99%
“…It is also not known, though tempting to speculate, whether a CRKL ± STAT5 heterodimer formed via their SH2 domains would allow the CRKL SH3 domains to bring additional enzymes, for example kinases like c-Abl or HPK1 into the nucleus. c-Abl is well known to have nuclear functions (Shaul, 2000;Wang, 2000) and both HPK1 and c-Abl can phosphorylate c-Jun in vitro (Barila et al, 2000;EK Schmidt and SM Feller, unpublished data). Furthermore, c-Abl and HPK1 were found to bind to each other upon experimentally-induced DNA-damage (Ito et al, 2001).…”
Section: Stat5mentioning
confidence: 95%